Outcomes of home‐based primary care for homebound older adults: A randomized clinical trial. Issue 2 (20th August 2022) - Federman, Alex D.; Brody, Abraham; Ritchie, Christine S.; Egorova, Natalia; Arora, Arushi; Lubetsky, Sara; Goswami, Ruchir; Peralta, Maria; Reckrey, Jenny M.; Boockvar, Kenneth; Shah, Shivani; Ornstein, Katherine A.; et al.
Abstract: Background: Homebound older adults are medically complex and often have difficulty accessing outpatient medical care. Home‐based primary care (HBPC) may improve care and outcomes for this population but data from randomized trials of HBPC in the United States are limited. Methods: We conducted a randomized controlled trial of HBPC versus office‐based primary care for adults ages ≥65 years who reported ≥1 hospitalization in the prior 12 months and met the Medicare definition of homebound. HBPC was provided by teams consisting of a physician, nurse practitioner, nurse, and social worker. Data were collected at baseline, 6‐ and 12‐months. Outcomes were quality of life, symptoms, satisfaction with care, hospitalizations, and emergency department (ED) visits. Recruitment was terminated early because more deaths were observed for intervention patients. Results: The study enrolled 229 patients, 65.4% of planned recruitment. The mean age was 82 (9.0) years and 72.3% had dementia. Of those assigned to HBPC, 34.2% never received it. Intervention patients had greater satisfaction with care than controls (2.26, 95% CI 1.46–3.06, p  < 0.0001; effect size 0.74) and lower hospitalization rates (−17.9%, 95% CI −31.0% to −1.0%; p  = 0.001; number needed to treat 6, 95% CI 3–100). There were no significant differences in quality of life (1.25, 95% CI −0.39–2.89, p  = 0.13), symptom burden (−1.92, 95% CI −5.22–1.37, p  = 0.25) or ED visits (1.2%, 95% CI −10.5%–12.4%; p  = 0.87). There were 24 (21.1%) deaths among intervention patients and 12 (10.7%) among controls ( p  < 0.0001). Conclusion: HBPC was associated with greater satisfaction with care and lower hospitalization rates but also more deaths compared to office‐based primary care. Additional research is needed to understand the nature of the higher death rate for HBPC patients, as well as to determine the effects of HBPC on quality of life and symptom burden given the trial's early termination. Abstract : See related Editorial by Boling et al . in this issue.